Increment analysis in black locust (Robinia pseudoacacia L.) stand – a case study - Rédei, K.; Ábri, T. (International Journal of Horticultural Science, 2021)
The study on the diameter and volume increment of black locust (Robinia pseudoacacia L.) stand (age 10-27 years, yield class II) have shown that in comparison to the periodic annual increment of the breast height diameter of tree in height class I, trees in height class II have reached 83.3%, while in class III only 43.9. The same relations for volume were found 59.0% and 24.5%, respectively. The mean values of the whole stand were close to those of height class II. According to the distribution of the periodic annual increment of volume between 10 and 27 years of age, 50% of the values were between 2.00 and13.88 dm3, 73% were between 2.00 and19.82 dm3, and 96% were between 2.00 and 37.64 dm3. The range of 13.88–19.82 dm3 had the highest occurrence (24.5%).